5-HT3 antagonist ondansetron--an effective outpatient antiemetic in cancer treatment. Issue 8 (August 1990) - Pinkerton, C R; Williams, D; Wootton, C; Meller, S T; McElwain, T J
Abstract : Thirty children aged 2-16 years with malignant tumours who were receiving chemotherapy were treated with the 5-HT3 antagonist ondansetron. Each received a single intravenous dose (5 mg/m2) followed by oral doses (2-4 mg depending on surface area) every eight hours for five days. Chemotherapy regimens comprised: carboplatin alone, carboplatin plus etoposide, cisplatin plus etoposide; adriamycin (doxorubicin) plus cyclophosphamide, or ifosfamide. Twelve patients received ondansetron with their first course of chemotherapy and the other patients were poor responders to previous antiemetic treatment. Efficacy was assessed by a questionnaire documenting the incidence of vomiting and severity of nausea. In a 24 hour period after starting chemotherapy a complete or major response (less than two vomiting episodes) was achieved in 87% of children. Although ondansetron was effective for early antiemesis after cisplatin or ifosfamide, delayed vomiting, retching, or nausea reduced responses to 50% and 20%, respectively. We conclude that in children ondansetron is an effective, well tolerated, oral antiemetic enabling simple administration in the outpatient setting. In the present schedule it was of limited efficacy against cisplatin or ifosfamide induced emesis.